2022
DOI: 10.1002/slct.202104147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quercetin Functionalized Silver Nanoparticles and Their Application for the Colorimetric Detection of L‐Cysteine in Biologically Complex Fluids

Abstract: In the present manuscript authors report an eco‐friendly, simple, and cost‐effective one‐pot synthesis of quercetin functionalized silver nanoparticles (Q‐AgNPs). The synthesized Q‐AgNPs exhibited surface plasmonic resonance absorption band at 418 nm which confirmed the synthesis. The synthesized Q‐AgNPs were further characterized by X‐ray diffraction which confirmed the crystalline structure of Q‐AgNPs. FTIR analysis of Q‐AgNPs was performed to find out the functional groups present on Q‐AgNPs. The distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…In the context of medication compatibility testing, FTIR analysis of Qu-AgNPs was performed, as depicted in Figure 2. It was observed that all spectral groups exhibited consistent values, affirming the authenticity of the drug sample and confirming the absence of any discernible impurities [29].…”
Section: Ftir Study Of Qu Nanoparticlessupporting
confidence: 63%
“…In the context of medication compatibility testing, FTIR analysis of Qu-AgNPs was performed, as depicted in Figure 2. It was observed that all spectral groups exhibited consistent values, affirming the authenticity of the drug sample and confirming the absence of any discernible impurities [29].…”
Section: Ftir Study Of Qu Nanoparticlessupporting
confidence: 63%
“…E. uniflora L. phytochemicals, such as saponin, tannins, phenolic compounds, and flavonoids [ 51 , 52 ], interact with AgNO 3 reduced to elemental silver or gold. Biosynthesis probably involves quercetin [ 53 ], carotenoids, and luteolin [ 54 ]. The presence of silver nanoparticles is confirmed in Figure 2 b.…”
Section: Discussionmentioning
confidence: 99%
“…9 Considering the aforementioned properties, the detection of l -cysteine is of great significance for human health and food quality assurance. To date, researchers have developed a multitude of analytical techniques for l -cysteine detection, for instance, chromatography, 10 electrochemistry, 11 colorimetry, 12 and so on. However, despite their superior performance in detecting l -cysteine, their applications are limited by the unavailability of large-scale equipment, complicated sample pretreatment, and laborious operation processes.…”
Section: Introductionmentioning
confidence: 99%